2019
DOI: 10.11130/jei.2019.34.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Integration Matter for Financial Development? Evidence from the East Asian and Pacific Region

Abstract: This paper assesses the impact of financial integration on financial development and establishes thresholds for materializing gains of financial advances from financial globalization using a sample of 34 countries from the East Asian and Pacific region. Following the approaches of Kose et al. (2011) and Asongu and De Moor (2016), we test non-linearity within the financial openness and financial development nexus through semi-parametric ordinary least-squares regression, and then, we develop threshold dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In exploring the non‐linear behavior of AML regulations with growth as well as the FDI–growth nexus, we employ the panel threshold regression approach suggested by Hansen (2000). Traditionally, the threshold effect is assessed by introducing a quadratic term in the model (see Aibai et al, 2019; Ibrahim & Alagidede, 2018; Taghizadeh‐Hesary et al, 2019). However, this approach is unable to identify the exact point where the relationship changes direction.…”
Section: Methodsmentioning
confidence: 99%
“…In exploring the non‐linear behavior of AML regulations with growth as well as the FDI–growth nexus, we employ the panel threshold regression approach suggested by Hansen (2000). Traditionally, the threshold effect is assessed by introducing a quadratic term in the model (see Aibai et al, 2019; Ibrahim & Alagidede, 2018; Taghizadeh‐Hesary et al, 2019). However, this approach is unable to identify the exact point where the relationship changes direction.…”
Section: Methodsmentioning
confidence: 99%
“…Again, the impact of AML regulations on the financial sector development may not be constant over time. In examining the threshold effects, the traditional technique is by introducing the quadratic term of the threshold variable (see Aibai, Huang, Luo, & Peng, 2019; Ibrahim & Alagidede, 2018; Taghizadeh‐Hesary, Phi, Hong, & Chu, 2019). This approach may be prone to multicollinearity problems and unable to address potential structural breaks that may occur in a relatively long period (Huang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This study therefore departs from previous studies by employing Hansen (2000) sample splitting estimation technique, which is capable of tracing the turning point or the threshold for policy decisions. Therefore, we apply the panel threshold analysis by Hansen (2000) and applied in recent literature (Huang et al, 2018; Liu et al, 2020; Luan, Huang, & Zou, 2019; Ouyang et al, 2019; Sare, 2019; Taghizadeh‐Hesary et al, 2019) in examining the changes in the financial sector following changes in anti‐money laundering regulations. We investigate the impact of AML regulations on financial sector development at different levels or intervals of AML regulations.…”
Section: Methodsmentioning
confidence: 99%
“…Due to East Asia's deepening economic relations, changing political landscape and special market conditions (Lall and Teubal, 1998; Yeung, 2009), a number of previous studies have confirmed that economic and financial integration in East Asia has been driven by trade linkages and investment movements (Didier et al. , 2017; Jin, 2018; Taghizadeh-Hesary et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%